(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
Because of its massive population, India is a big market for Fast-Moving Consumer Goods (FMCG) firms. There are currently a number of large and minor companies on the market with substantial clout. The purpose of this article is to examine why the Patanjali brand has grown so quickly in the market. It is apparent that Patanjali’s path has not been simple, since Patanjali is a relatively young company. However, Patanjali’s positioning, branding, and eventual strategy to build consumer confidence and trust made a difference, and Patanjali’s market share grew so quickly that it overtook numerous items from well-known brands in only 2 to 3 years, propelling it to the top of the market. Ramdev’s marketing approach was executed flawlessly in the market, and his key formula was "swadeshi," which worked wonders in attracting a large number of consumers as well as a huge proportion of raw material suppliers, i.e. Indian farmers. It is still necessary to promote locally grown and made goods.